Rediscovering the (Center for West Visayan Studies) as a cultural institution. - Jover, Elmer Labra
The study seeks to find meaning and significance in the Center for West Visayan Studies (CWVS) as a structure of knowledge in Wetern Visayas. In here, the historical profile of the place (with its development) served as the source of information in establishing the notion that the CWVS satisfies the elements of a knowledge structure. These elements are the institution's purpose, it demonstrated concepts, the contextual logic that affects its operation and its implications to the reflective learners of society. The study concludes that the CWVS, by being a knowledge structure, is needed more than just a neutral institution that caters to the need of the people. It is an institution that exercises the power to represent West Visayan culture, as well as the technological innovations that the region has achieved. Research works, publications, exhibits and other demonstrations are examples of such representations. Here, the object of study are constinously re-discovered and re-defined by the CWVS. Interestingly, this re-definition allows a form of `maneuvering' on the part of the CWVS --- the re-production of knowledge in Western Visayas and the eventual increase of its power as a knowledge structure.